Applications of Thermoregulation Adaptive Technique of form in Nature into Architecture: A Review - Abdullah, Amatalraof; Bin Said, Ismail; Remaz Ossen, Dilshan (International Journal of Engineering and Technology, 2018)
In the last 20 years, biology has obviously been the source of countless, innovative solutions from nature in many discipline. Biomimetic is an interesting philosophy which hybrids multi-disciplinary sciences with biology.  Biomimetic design is currently one of the promising fields ranging from accessing to adaptive, sustainable and energy saving solutions for the architectural and environmental challenges. This paper underlines and reviews the recent state of the art biomimetic applications to architecture, in particular, thermoregulation strategies. The review design was based on project’s status that varies from executed projects, experimental models and design concepts.  The study shows that biomimicking thermoregulation strategies of the nature leads to a significant energy saving and indoor thermal comfort. It is also observed that some of the architectural researches in this regard do not exceed the stage of theoretical study due to the lack of sponsorship and funding. Although there is a number of levels in respect to mimicking adaptive notions from nature such as behavioral, physiological, and morphological, architects’ works are mostly confined to mimicking the functional performance of organism through its morphological configuration; physiological and morphological adaptation. The review shows that architects turn noticeably to nature’s solutions as the source of zero-waste system, saving energy and controlling thermal environment.